Conjunctival bacterial flora in healthy individuals and health care workers (HCWs) (Bangladesh Journal of Medical Microbiology, 2012)
This study was designed to see the pattern of conjunctival bacterial flora in healthy individuals and health care workers. This prospective study was conducted during the period of January 2011 to December 2011 in BSMMU. A total of 480 conjunctival swabs were collected from both eyes of 200 healthy individuals and 40 HCWs of BSMMU. Significant number of culture was positive in HCWs (52.5%) compared to healthy individuals (23.75%). Staphylococcus epidermidis was predominant in healthy individuals (65.26%) and HCWs (66.66%). Isolation of Enterocooci (11.9%) was significantly higher in HCWs. Bilateral culture positivity was significantly higher in HCWs (71.43%) than that from healthy individual (40%) and in healthy individuals, unilateral culture positivity was 60%, which was higher than that of HCWs (28.57%).DOI: http://dx.doi.org/10.3329/bjmm.v6i2.19371 Bangladesh J Med Microbiol 2012; 06(02): 15-19